2015
DOI: 10.1371/journal.pone.0132515
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Brain Tumor Recurrence from Post-Radiotherapy Necrosis with 11C-Methionine PET: Visual Assessment versus Quantitative Assessment

Abstract: PurposeThe aim of this multi-center study was to assess the diagnostic capability of visual assessment in L-methyl-11C-methionine positron emission tomography (MET-PET) for differentiating a recurrent brain tumor from radiation-induced necrosis after radiotherapy, and to compare it to the accuracy of quantitative analysis.MethodsA total of 73 brain lesions (glioma: 31, brain metastasis: 42) in 70 patients who underwent MET-PET were included in this study. Visual analysis was performed by comparison of MET upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 25 publications
7
49
3
2
Order By: Relevance
“…Several studies have shown that MET PET/CT is useful for distinguishing tumor recurrence from radiation-induced necrosis. [13][14][15] The major advantage of this technique is that the tracer is thought to accumulate preferentially in tumor tissue, resulting in good contrast against the normal tissue in the background. Similar to a previous study, 16 all cases that showed negative results on visual assessment were those with radiation injury.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that MET PET/CT is useful for distinguishing tumor recurrence from radiation-induced necrosis. [13][14][15] The major advantage of this technique is that the tracer is thought to accumulate preferentially in tumor tissue, resulting in good contrast against the normal tissue in the background. Similar to a previous study, 16 all cases that showed negative results on visual assessment were those with radiation injury.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate, non-invasive characterization of solid tumors during and following radiation treatment is important for monitoring therapeutic response and guiding subsequent treatment planning (Lupo and Nelson, 2014; Minamimoto et al , 2015; Schmainda, 2012). Response is often monitored by measuring changes in tumor volume, using magnetic resonance imaging (MRI) or X-ray computed tomography (CT), weeks to months following radiation treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This has also been demonstrated in patients with brain metastases who underwent radiosurgery for brain metastases treatment [80,81]. The diagnostic accuracy of [ 11 C]MET PET regarding this clinical question is slightly lower (approximately 75%) [8,82,83], which is most probably related to the higher affinity of [ 11 C]MET for inflammation [84]. First PET studies using [ 11 C]AMT or [ 18 F]FACBC suggest that these tracers may also be of value for the differentiation of radiation injury from glioma progression [85,86].…”
Section: Value Of Amino Acid Pet Tracers For Brain Tumor Patientsmentioning
confidence: 81%